HUBUNGAN ANTARA REHABILITASI DAN DUKUNGAN KELUARGA DENGAN KEJADIAN STROKE BERULANG (STUDI KASUS DI RSUD Dr. ADHYATMA, TUGUREJO SEMARANG) - Kinanti Fajar Cahyaning Tyas; Ari Udiyono; Lintang Dian Saraswati; Henry Setyawan Susanto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Regional General Hospital dr. Adhyatma Tugurejo Semarang is the second largest hospital with stroke cases with a prevalence in 2015 of 9%. The prevalence of recurrent stroke in 2015 was 5%, increasing from last year by 3%. The purpose of this study case is to study the risk factors that are caused recurrent stroke (study case at dr. Adhyatma Tugurejo Hospital Semarang). This research was an observational with approach case control study. The sample of research with 122 respondents who selected by recording all stroke patients in 2015 and repeated strokes in 2016, then conducted interviews using a questionnaire. Data were analyzed by frequency distribution and bivariate using the chi-square statistical test. The results of the research are there was no relationship between rehabilitation and family support with recurrent stroke.. Suggestions for the need for family care or support related to patient recovery, not returning to smoking, and fully controlling the risk factors for recurrent recovery by diligently conducting a health check.